Digital Transformation in Foreign Surveillance: A Systematic Literature Review (SLR) of the Role of Geospatial Intelligence - Prima Setiawan; Hari Purwanto; Budi Prasetyono; Somantha Prakosa Jati (UIR PRESS, 2025)
Surveillance of foreigners is essential in maintaining Indonesia's national stability and security, given the increasing global migration mobility. Digital transformation and the application of geospatial intelligence (Geoint) are potential solutions to improve the detection and early response to threats brought by foreign nationals (WNA). This study aims to evaluate the effectiveness of geospatial intelligence (Geoint) in enhancing the surveillance of foreign nationals (WNA) within the context of Indonesia’s national security and stability. This study uses a Systematic Literature Review (SLR) based on the PRISMA 2020 guidelines, with literature searches on Scopus and Google Scholar until May 10, 2024. The selected studies focused on the use of Geoint in relation to immigration and national security surveillance, while studies that were irrelevant or not available in full text were excluded. The findings indicate that Geoint significantly enhances surveillance capabilities by enabling rapid, precise monitoring and early threat prediction. Notably, Geoint facilitates the analysis of movement patterns of foreign nationals and the identification of high-risk areas, thereby increasing operational efficiency and targeting accuracy. For instance, it supports proactive responses to espionage-related activities—defined as the illicit gathering of sensitive information—that pose a risk to national security. The study concludes that integrating Geoint into immigration surveillance systems represents a strategic advancement in Indonesia’s digital security infrastructure. For policymakers and security practitioners, this innovation underscores the need for adaptive, data-driven surveillance frameworks that can respond dynamically to evolving migration patterns and security threats. Future national security policies should consider institutionalizing Geoint as a core component of foreign surveillance strategy.